2019
DOI: 10.1186/s12986-019-0394-z
|View full text |Cite
|
Sign up to set email alerts
|

Moderate physical exercise improves lymphocyte function in melanoma-bearing mice on a high-fat diet

Abstract: Background Obesity can lead to a chronic systemic inflammatory state that increases the risk of cancer development. Therefore, this study aimed to evaluate the alterations in tumor non-infiltrated lymphocytes function and melanoma growth in animals maintained on a high-fat diet and/or moderate physical exercise program in a murine model of melanoma. Methods Female mice were randomly divided into eight groups: 1) normolipidic control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 70 publications
(71 reference statements)
1
14
0
2
Order By: Relevance
“…This is an intensity of exercise that can be performed regularly daily even in obese mice and does not mean high-resistance or exhaustive exercise. In our opinion, the high-intensity exercise protocol in this study may be close to a regular moderate exercise protocol in other many previous studies (Baek et al, 2018a;Baek et al, 2018b;Baek et al, 2019;Dos Santos et al, 2019). Therefore, in actual clinical applications, these facts must be reflected to set exercise intensity.…”
Section: Discussionsupporting
confidence: 72%
“…This is an intensity of exercise that can be performed regularly daily even in obese mice and does not mean high-resistance or exhaustive exercise. In our opinion, the high-intensity exercise protocol in this study may be close to a regular moderate exercise protocol in other many previous studies (Baek et al, 2018a;Baek et al, 2018b;Baek et al, 2019;Dos Santos et al, 2019). Therefore, in actual clinical applications, these facts must be reflected to set exercise intensity.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, a physical activity prior to tumor cells inoculation led to a strong reduction of primary tumor growth and numbers of lung metastasis in those mice. Other study demonstrated that the growth of B16F10 melanoma in mice on high-fat diet was accelerated as compared to mice receiving a balanced diet [114]. Importantly, this growth increase was significantly reduced by continuous physical exercise that was associated with the lymphocyte proliferation [114].…”
Section: Increasing Effectiveness Of Ici Therapymentioning
confidence: 96%
“…Other study demonstrated that the growth of B16F10 melanoma in mice on high-fat diet was accelerated as compared to mice receiving a balanced diet [114]. Importantly, this growth increase was significantly reduced by continuous physical exercise that was associated with the lymphocyte proliferation [114]. In melanoma patients, exercises undertaken before diagnosis were not significantly correlated with a reduction in cancer-related or overall mortality [115].…”
Section: Increasing Effectiveness Of Ici Therapymentioning
confidence: 98%
“…Daneben bewirkte körperliche Aktivität vor der Tumorzellinokulation bei diesen Mäusen einen starken Rückgang des Primärtumorwachstums und der Anzahl von Lungenmetastasen. In einer anderen Studie war das Wachstum des B16F10-Melanoms bei Mäusen, die fettreich ernährt wurden, im Vergleich zu Mäusen, die eine ausgewogene Ernährung erhielten, beschleunigt [114]. Bedeutsam ist dabei, dass diese Wachstumszunahme durch kontinuierliche körperliche Bewegung, die mit der Proliferation von Lymphozyten verbunden war, signifikant verringert wurde [114].…”
Section: Wirksamkeitssteigerung Der Ici-therapieunclassified
“…In einer anderen Studie war das Wachstum des B16F10-Melanoms bei Mäusen, die fettreich ernährt wurden, im Vergleich zu Mäusen, die eine ausgewogene Ernährung erhielten, beschleunigt [114]. Bedeutsam ist dabei, dass diese Wachstumszunahme durch kontinuierliche körperliche Bewegung, die mit der Proliferation von Lymphozyten verbunden war, signifikant verringert wurde [114]. Bei Melanom-Patienten fand sich keine signifikante Korrelation zwischen sportlichen Aktivitäten vor der Diagnose und dem Rückgang der krebsbedingten oder Gesamtmortalität [115].…”
Section: Wirksamkeitssteigerung Der Ici-therapieunclassified